LIVING CURRICULUM AND PARTICIPATORY MANAGEMENT: THEORETICAL FOUNDATIONS FOR A DEMOCRATIC SCHOOL BASED ON FREIRE, HERNÁNDEZ AND HONNETH - de Aguiar Costa, Julimar (Revista Gênero e Interdisciplinaridade, 2026)
This article presents a theoretical reflection on the foundations of a curriculum conceived as a living construction and a school guided by participatory management. Based on the references mobilized in the author’s thesis – especially Paulo Freire, Fernando Hernández, Lev Vygotsky, José Gimeno Sacristán, Axel Honneth and Charles Taylor – the text discusses three central axes: the curriculum as a dynamic social practice, beyond its prescribed and hidden dimensions; affectivity as a structuring element of learning and pedagogical relationships; and student protagonism as an expression of democratic management and intersubjective recognition. The article concludes that building a democratic school requires overcoming technicist models and valuing subjectivity, dialogue and co-responsibility.